Polyphenol-Rich Extract from Murta Leaves on Rheological Properties of Film-Forming Solutions Based on Different Hydrocolloid Blends - Silva-Weiss, A (Elsevier Ltd, 2014)
Film-forming solutions (FFS) based on sodium carboxymethylcellulose (CMC), low and high molecular weight fish-skin gelatin (LG and HG), unmodified and modified corn starch (CS and MS) and chitosan (CH) were prepared. Seven binary blends were evaluated (CH-CMC, CH-CS, CS-CMC, MS-CMC, HG-CMC and LG-CMC). The rheological properties of FFS and blends were studied as a function of the hydrocolloid blend type and as a function of polyphenol-rich extract from murta leaves (Ugni molinae Turcz) (PEML) in FFS. Steady-state flow tests and oscillatory measurements within the linear viscoelasticity region (LVR) were carried out. Flow behavior of FFS was significantly affected by the hydrocolloid blend type as well as presence or absence of PEML in the matrix. FFS behaves as non-Newtonian and pseudoplastic fluid above 0.4 s-1 shear rate. The PEML formed aggregates with chitosan, leading to a gel-like structure with thirotropic behavior on CH and CH-CS solutions. PEML induced thermal stability in CH-CMC FFS. The FFS based on LG-CMC and HG-CMC were unstable with frequency when PEML was added. The FFS based on CS-CMC, MS-CMC, and CMC behaved as homogeneus solution, either without or with PEML. The viscosity, ranging between 2.75 and 8.49 Pa s to 2 s-1 at 25 °C, was suitable for the casting process and provided stable solutions in the wide frequency range and temperature studied. © 2014 Elsevier Ltd. All rights reserved.